Peculiairities of mRNA TLR-2, TLR-4 expression of the oral cavity epithelium in children under conditions of chronic catarrhal gingivitis and diabetes mellitus - А. V. Kotelban; О. І. Godovanets; G. D. Koval; О. М. Kamyshnyi (Zaporožskij Medicinskij Žurnal)
TLRs in Epithelium of the oral cavity can be effected as due to the dental as general somatic pathology. TLR availability in the external membrane of neutrophils, macrophages, keratocytes was found to be a starting point in triggering inflammation in the periodontal tissues ensuring molecular reception of a pathogen with further involvement of important components in the inherited immunity. These effectors possess phagocytic and killer activities, ensure a number of signals activating and directing antigen-specific response by the cells of the adaptive immune system.